دور الافصاح المحاسبي في تحسين المعلومة المحاسبية للقاوئم المالية - أحمد قايد, نورالدين; بن زاف, لبنى (جامعة الوادي - University of Eloued, 2018)
تهدف هـذه الدراسـة إلى تنـاول موضـوع الإفصـاح المحاسـبي وأثره في تحسين المعلومـة المحاسبية للقوائم المالية الذي يعتبر من الأمور المهمة في المحاسبة المالية، فالإفصاح المحاسبي هو الذي يقدم المعلومات المحاسبية لمسـتخدميها بشيء من التفصيل والشفافية من دون لبس أو تضليل. من أهم النتائج المتوصل إليها أن الإفصــاح المحاســبي سـوف يكـون لـه أثـر ايجـابي علـى المعلومـة المحاسـبية لمـا سيوفره من خصائص نوعية للمعلومة المحاسبية أهمها الملائمة والموثوقية، وبالتالي بعث ثقة للمستثمر فيها. Abstract : The aim of this study is to address the issue of accounting disclosure and its impact on improving accounting information for financial statements, which is considered important in financial accounting. Accounting disclosure provides accounting information to its users in some detail and transparency without any ambiguity or shading. One of the most important findings is that accounting disclosure will have a positive effect on the accounting information as it will provide the qualitative characteristics of the accounting information, the most important of which is the appropriateness and reliability, and thus instill confidence in the investor.
The role of accounting disclosure in improving accounting information for financial statements:
مقال
Keywords: الافصاح المحاسبي؛ المعلومة المحاسبية؛ القوائم المالية; Accounting Disclosure, Accounting Information, Financial Statements.